2020
DOI: 10.2337/db20-0009
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Glucocorticoids During Pregnancy Impair Fetal Brown Fat Development and Predispose Offspring to Metabolic Dysfunctions

Abstract: Maternal stress during pregnancy exposes fetuses to hyperglucocorticoids, which increases the risk of metabolic dysfunctions in offspring. Despite being a key tissue for maintaining metabolic health, the impacts of maternal excessive glucocorticoids (GC) on fetal brown adipose tissue (BAT) development and its long-term thermogenesis and energy expenditure remain unexamined. For testing, pregnant mice were administered dexamethasone (DEX), a synthetic GC, in the last trimester of gestation, when BAT development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 49 publications
0
31
1
1
Order By: Relevance
“…Some studies have also shown that changes in offspring adiposity with gestational hypoxia are coupled with changes in DNA methylation patterns in the adipose tissue [101,142]. There was also increased DNA methylation of the Ppargc1a promoter in neonatal BAT and brown adipocyte progenitor cells, which was linked with attenuated BAT development in response to glucocorticoid over-exposure during gestation [125]. Finally, the methylation of multiple genes was aberrant in the visceral WAT of infant and adult offspring exposed to excess androgens, which likely contributed to the development of obesity and PCOS in the experimental model [133].…”
Section: Epigenetic Mechanismsmentioning
confidence: 97%
See 1 more Smart Citation
“…Some studies have also shown that changes in offspring adiposity with gestational hypoxia are coupled with changes in DNA methylation patterns in the adipose tissue [101,142]. There was also increased DNA methylation of the Ppargc1a promoter in neonatal BAT and brown adipocyte progenitor cells, which was linked with attenuated BAT development in response to glucocorticoid over-exposure during gestation [125]. Finally, the methylation of multiple genes was aberrant in the visceral WAT of infant and adult offspring exposed to excess androgens, which likely contributed to the development of obesity and PCOS in the experimental model [133].…”
Section: Epigenetic Mechanismsmentioning
confidence: 97%
“…This was coupled with alterations in adipocyte morphology, expression of lipogenic genes, insulin signaling proteins and inflammatory cytokine expression in the offspring WAT [124]. There were also cellular and molecular changes in the BAT of offspring overexposed to glucocorticoids prenatally, namely decreased UCP1 expression, increased lipid droplet size, upregulated prolactin receptor and decreased mitochondria content, which would be expected to compromise tissue function [64,125]. However, sex effects have not been explored and further work is required to identify the importance of length, timing and level of glucocorticoid over-exposure during gestation to the developmental programming of offspring adipose biology and obesity.…”
Section: Glucocorticoids and Offspring Adipositymentioning
confidence: 99%
“…Epigenetic regulation during fetal development can alter the gene expression profile in the offspring, which may predispose them to either health or disease susceptibilities in adult life 45,46 . Among the targets analyzed ( Gck , Abcc8.1 , Camk2d , and Hnf4a ) we did not identify any epigenetic effect by DEX exposure during gestation.…”
Section: Discussionmentioning
confidence: 71%
“…Alterations in PGC1α expression were more pronounced in the SDF than BF and were accompanied by parallel changes in SDF expression of MFN2 , a gene essential for normal membrane dynamics and OXPHOS function that is regulated by PGC1α ( Liang & Ward 2006 ). Previous studies on rodents have shown that PGC1α expression is glucocorticoid sensitive and increases towards term in fetal heart and adipose tissue ( Rog-Zielinska et al 2015 , Chen et al 2020 ). Deletion of PGC1α expression in fetal mice also impairs mitochondrial OXPHOS function and the metabolic response to glucocorticoids in developing cardiomyocytes ( Rog-Zielinska et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%